A spectroscopic method for quantitating lignin in lignocellulosic biomass based on the completely dissolved solution of biomass in LiCl/DMSO. Issue 5 (18th February 2022) - Zhang, Haonan; Zhao, Hui; Yang, Yan; Ren, Hao; Zhai, Huamin
Abstract : A green method for lignin quantitation based on the completely dissolved solution of lignocellulosic biomass in LiCl/DMSO and UV spectrophotometry was developed. The method is accurate, sensitive, mild, and does not use hazardous reagents. Abstract : The quantitation of lignin is essential for the evaluation, conversion, and utilization of lignocellulosic biomass. However, the existing lignin quantitation methods like the widely used Klason method still have some disadvantages, such as requiring hazardous reagents, complicated steps, heating, introducing interfering substances, and low sensitivity. In this study, a novel green method for lignin quantitation based on the completely dissolved solution of lignocellulosic biomass in LiCl/DMSO and UV spectrophotometry (LiCl/DMSO CDS-UV method) was developed. The process does not require complex chemical pretreatment and separation of lignin from lignocellulosic biomass. The biomass samples extracted with benzene/ethanol (v/v 2 : 1) can be completely dissolved in an 8% LiCl/DMSO solvent system at room temperature (25 °C) and atmospheric pressure after short-time ball milling (3 h). For the chemical delignified samples with a low lignin content, the completely dissolved solution can be obtained only by heating the solution to 60 °C and stirring at atmospheric pressure for 2 h. Then the lignin content of the solution was determined by UV spectrophotometry. Different species of biomass including herbage (wheat straw), hardwood (black poplar), softwood (redwood), bark (eucalyptus bark and redwood bark), and above biomass treated by different delignification methods and degrees were applied to establish the LiCl/DMSO CDS-UV method and extend the applicability of this method. The results quantified by the LiCl/DMSO CDS-UV method were compared with the total lignin content measured by the Klason method and a good correlation was observed. The LiCl/DMSO CDS-UV method only requires trace samples (0.1 g) to achieve a precise determination of the lignin content, the conditions are mild, no hazardous reagents are used and no interfering substances are produced in the process.